PRODUKTIVITAS KERJA GURU MADRASAH DI KAWASAN INDUSTRI KABUPATEN BEKASI - Dermawati Dermawati (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2016)
Pedagogic and professional competence should be acquired by teachers in order to gain maximum work productivity whose effect is on the quality of the graduates. Teacher work productivity is strongly influenced by the environment surrounding the madrasah/ schools, i.e. industrial area. This research aims at investigating teachers’ productivity from the aspects of pedagogic competence and professional competence in the industrial area of Bekasi regency. The study was conducted in ten Madrasah Tsanawiyah (Islamic primary schools) by collecting data from surveys and interviews. The data were then analyzed through content analysis. The study found out that 48% of teachers (29 teachers) obtained pedagogic competence below 60%, and 82% of them (49 teachers) obtained professional competence below 60%. It can be concluded that the industrial area is 100% uncorrelated and uninfluential to the teachers’ work discipline, instead it affects the work productivity. This study suggests the schools to conduct teachers’ performance assessment to identify teacher competence in the industrial area of Bekasi. It also suggests the schools to conduct more professional development programs to improve teachers’ competence focusing on pedagogic competence and professionalism competence. KEY WORDS: Teachers’ work productivity, industrial area, madrasah tsanawiyah